DIALECT AND GENDER IN SOCIOLINGUISTIC PERSPECTIVE - Dinata, Yudistira; Rifqy F , Ananda Dany; Nargis, Nargis (Media Inovasi Pendidikan dan Publikasi, 2025)
This research addresses the relationship between dialect and gender in the realm of sociolinguistics. The main focus is on how gender differences affect the choice of dialect and language forms used in various social contexts. This study seeks to explore the social and cultural factors that contribute to language variation based on gender. Through this research, it is hoped to provide new insights into the influence of gender on language in social interaction.